High Endothelial Venules: A Vascular Perspective on Tertiary Lymphoid Structures in Cancer - Vella, Gerlanda; Guelfi, Sophie; Bergers, Gabriele (Frontiers in Immunology, 2021)
High endothelial venules (HEVs) are specialized postcapillary venules composed of cuboidal blood endothelial cells that express high levels of sulfated sialomucins to bind L-Selectin/CD62L on lymphocytes, thereby facilitating their transmigration from the blood into the lymph nodes (LN) and other secondary lymphoid organs (SLO). HEVs have also been identified in human and murine tumors in predominantly CD3+T cell-enriched areas with fewer CD20+B-cell aggregates that are reminiscent of tertiary lymphoid-like structures (TLS). While HEV/TLS areas in human tumors are predominantly associated with increased survival, tumoral HEVs (TU-HEV) in mice have shown to foster lymphocyte-enriched immune centers and boost an immune response combined with different immunotherapies. Here, we discuss the current insight into TU-HEV formation, function, and regulation in tumors and elaborate on the functional implication, opportunities, and challenges of TU-HEV formation for cancer immunotherapy.